PCR-based DGGE Identification of Bacteria Present in Pasteurised South African Fruit Juices - Duvenage, W.; Gouws, P.A.; Witthuhn, R.C. (South African Journal of Enology and Viticulture, 2016)
The contamination of pasteurised fruit juice products by thermophilic acidophilic bacteria (TAB) has become a concern for producers. The aim of this study was to identify the bacteria present in South African fruit juices before and after pasteurisation, using polymerase chain reaction (PCR)-based denaturing gradient gel electrophoresis (DGGE). Alicyclobacillus acidoterrestris was found to be present in apple, pear, white grape and aloe vera juice. White grape juice was found to contain Alicyclobacillus pomorum, while two uncultured bacteria in the orange, apple, mango and pear juices were presumptively identified as members of the genus Bacillus, and one uncultured bacteria was identified as being closely related to Alcaligenes faecalis. The results emphasise the need for rapid and accurate detection of TAB in food products.